Application of edge computing technology in smart grid data security - Zhuo Cheng; Jiangxin Li; Jianjun Zhang; Chen Wang; Hui Wang; Juyin Wu (Measurement: Sensors)
Absrtact: In order to solve the problem that the two-way flow of power and information between user nodes and service nodes in the smart grid poses a huge threat to the privacy and security of user data, and at the same time, the limitation of the power bureau's computing resources also brings users response delay, service quality degradation and other problems, the author proposes the application of edge computing technology in smart grid data security. Combining with edge computing technology, the author proposes a proxy blind signcryption scheme based on certificateless without bilinear mapping. By blinding the power and information, the signcrypter can not know the specific power consumption information of the user, so as to ensure the data privacy and security of the user. Implement forward security using proxy key update mechanism and perform batch verification of user signature ciphertext. The experimental results indicate that: The total running time required for executing proxy authorization and verification, proxy key generation, signature and decryption algorithms in this scheme is 5.617 ms, with a ciphertext length of 80 Bytes. Compared with other existing literature, the maximum reduction is 85.6 % and 86 %, respectively. Conclusion: This scheme is more suitable for protecting data security and privacy in the data transmission process of smart grids due to its lower running time and communication cost.